2015
DOI: 10.2147/copd.s90673
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a respiratory rehabilitation exercise training package in hospitalized elderly patients with acute exacerbation of COPD: a randomized control trial

Abstract: Clinical trials identifierNCT02329873BackgroundAcute exacerbation (AE) of COPD is characterized by a sudden worsening of COPD symptoms. Previous studies have explored the effectiveness of respiratory rehabilitation for patients with COPD; however, no training program specific to acute exacerbation in elderly patients or unstable periods during hospitalization has been developed.ObjectiveTo evaluate the effects of a respiratory rehabilitation exercise training package on dyspnea, cough, exercise tolerance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%
“…The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd. only a few studies considered the effects of individual interventions of the physical therapy arsenal [20-22, 24, 27] and the effectiveness of pulmonary rehabilitation in a hospital environment at CoPd exacerbation [17,19,31,32] ( Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation